The role played by ailanthone in inhibiting bone metastasis of breast cancer by regulating tumor-bone microenvironment through the RANKL-dependent pathway - Wang, Yajun; Zhong, Zeyuan; Ma, Miao; Zhao, Yannan; Zhang, Chongjing; Qian, Zhi; Wang, Biyun (Frontiers in Pharmacology, 2023)
A majority of advanced Breast Cancer (BC) patients will have bone metastasis, while the osteolytic process is closely related to the osteophagocytic process of osteoclasts. Bone homeostasis is disrupted as a result of changes in inflammatory agents, cytokines, and other chemicals in the bone metastasis microenvironment. Ailanthus altissima shows an inhibitory effect on osteoclast differentiation. Ailanthone（AIL） refers to a natural compound isolated from Ailanthus altissima, a Chinese herbal medicine, and has effective anti-tumor activity in numerous cell lines. Its impact on bone metastases for BC is yet unclear. This study investigated the impact of AIL on BC, subsequent osteolytic bone degradation in breast cancer, and its potential mechanism of action. When experiments were conducted in mice with breast cancer bone metastases, it was noted that AIL prevented osteolytic bone degradation in vivo. The results further showed that when a safe concentration of AIL was used, it could significantly decrease the proliferative, migratory, and infiltration abilities of the MDA-MB-231 cells in vitro. It also reduced the expression of genes and proteins involved in osteoclast formation in MDA-MB-231 cells. The results of the bone resorption test, filamentous (F-actin) staining, and the Tartrate-resistant Acid Phosphatase (TRAP) staining tests implied that osteoclast cell differentiation of the Bone Marrow-derived Macrophages (BMMs), activated by the MDA-MB-231 cell Conditioned Medium (MDA-MB-231 CM) and the Receptor Activator of Nuclear factor-κB Ligand (RANKL), were suppressed by AIL in the concentration-dependent manner. Additionally, it inhibits osteoclast-specific gene and protein expression. It was noted that AIL inhibited the expression of the osteoclast differentiation-related cytokines RANKL and interleukin-1β (IL-1β) that were secreted by the MDA-MB-231 cells after upregulating the Forkhead box protein 3 (FOXP3) expression. Furthermore, AIL also inhibits the expression of the Mitogen-Activated Protein Kinase (MAPK), Phosphoinositide 3-kinase (PI3K)/ protein kinase B (AKT), and Nuclear factor-κB Ligand (NF-κB) signaling pathways, which then suppresses the MDA-MB-231CM-induced development of Osteoclasts. Thus, our study shows that AIL blocks osteoclast differentiation in the bone metastasis microenvironment by inhibiting cytokines secreted by BC cells, which may be a potential agent for the treatment of BC and its secondary bone metastasis.